Audience study on PRGA Program listservs - Villegas, Maria (CGIAR System-wide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovations, 2006)
In order to improve the PRGA Program information services, the PRGA Program Communications office decided to conduct an Audience Study, to learn more about how the subscribers are using PRGA Program's on-line tools (listservs and web site) and how they can be further improved. This document is the culmination of this survey including recommended courses of action that could be taken to improve audience participation.